Simulating the impact of natural disasters on urban development in a sample of earthquake - Satir, Onur; Kemec, Serkan; Yeler, Okan; Akin, Anil; Bostan, Pinar; Mirici, Merve Ersoy (Springer, 2023)
Natural disasters have been increased in areas, where people live densely, day by day. Istanbul 1999, Van 2011, and Izmir 2020 earthquakes were just some of the tragic events in the near past in Turkiye. The aim of this study was to define Van 2011 earthquakes effects as a sample on urban development by using land use/land cover projecting techniques. In this case, Van urban development (in urban macroform scale) was simulated without Van 2011 earthquakes based on existing urban development using the Cellular Automata Markov Chain (CA-MARKOV) approach for the year 2018. Effects of the earthquake were determined on urban development by comparing modeling results with observed 2018 built up areas. So that significant physical and social driving factors were evaluated including road distance, slope, hillshade, ground stability, and land use ability, and weighting values on urban development were calculated under the influence of the natural disaster. Van urban built up areas were mapped using high-spatial resolution remote sensing instruments such as SPOT, ASTER, RapidEye, and Gokturk 2 satellite dataset for 1988-2002-2011, and 2018 images applying an object-based classification approach (OBC). First of all, the model was validated using 1988, 2002, and 2011 urban development maps. The Kappa accuracy was found to be 0.85, respectively, for the model. Defined urbanization drivers were applied to the 2002-2011 time period to simulate 2018 urban areas without any earthquake. The results indicated that urban areas were affected by earthquakes. If there was no earthquake, urban development to the periphery would be 30% less. Additionally, 10% more built up areas would be constructed on ground sensitive areas, and only 2% of the new constructions would be established on suitable lands. Today this ratio is around 8%. As a result, urban development has been a trend to move from flat land to slight slopes and has been moved away from roads and settlements. It was determined that the spread into the city was accelerated as well as spread toward the periphery due to the earthquake.
Keywords: Remote sensing; Urban modeling; Urbanization; CA-MARKOV; GIS; Van City Turkiye